PSYCOLOGICAL AND PEDAGOGICAL ASPECTS OF USING COMPUTER SIMULATION IN TEACHING OF PLANNING AND ANALYSIS OF THE EXPERIMENT - Rackovych, Г.М. (Journal of Information Technologies in Education (ITE), 2014)
The article is devoted to the problem of increase the effectiveness of teaching students of planning and analysis of the experiment using the possibilities of computer simulation: experiments with the finished process models, special computer simulation systems.